A Further Look at the Propagation of Monetary Policy Shocks in HANK. Issue 6 (5th February 2021) - ALVES, FELIPE; KAPLAN, GREG; MOLL, BENJAMIN; VIOLANTE, GIOVANNI L.
Abstract: We provide quantitative guidance on whether and to what extent different elements of Heterogeneous Agent New Keynesian (HANK) models amplify or dampen the response of aggregate consumption to a monetary policy shock. We emphasize four findings. First, the introduction of capital adjustment costs does not affect the aggregate response, but does change the transmission mechanism so that a larger share of indirect effects originates from equity prices rather than from labor income. Second, incorporating estimated unequal incidence functions for aggregate labor income fluctuations leads to either amplification or dampening, depending on the data and estimation methods. Third, distribution rules for monopoly profits that allocate a larger share to liquid assets lead to greater amplification. Fourth, assumptions about the fiscal reaction to a monetary policy shock have a stronger effect on the aggregate consumption response than any of the other three elements.